Comparison of three common tonsil surgery techniques: cold steel with hot hemostasis, monopolar and bipolar diathermy - Knubb Jenny Christina; Kaislavuo Jasmin Maria; Jegoroff Henri Sebastian; Piitulainen Jaakko Matias; Routila Johannes (SPRINGER, 2025)
Purpose
To analyze the risk of postoperative hemorrhage in tonsil surgery with different surgical methods, instruments, indications, and age groups. Monopolar diathermy compared to bipolar diathermy was of particular interest.
Methods
The data from tonsil surgery patients were retrospectively collected between 2012 and 2018 in the Hospital District of Southwest Finland. The surgical method, instruments, indication, sex and age and their association with a postoperative hemorrhage were analyzed.
Results
A total of 4434 patients were included. The postoperative hemorrhage rate for tonsillectomy was 6.3% and for tonsillotomy 2.2%. The most frequently used surgical instruments were monopolar diathermy (58.4%) cold steel with hot hemostasis (25.1%) and bipolar diathermy (6.4%) with the overall postoperative hemorrhage rates 6.1%, 5.9% and 8.1%, respectively. In tonsillectomy patients, the risk for a secondary hemorrhage was higher with bipolar diathermy compared to both monopolar diathermy (p = 0.039) and the cold steel with hot hemostasis technique (p = 0.029). However, between the monopolar and the cold steel with hot hemostasis groups, the difference was statistically non-significant (p = 0.646). Patients aged > 15 years had 2.6 times higher risk for postoperative hemorrhage. The risk of a secondary hemorrhage increased with tonsillitis as the indication, primary hemorrhage, tonsillectomy or tonsillotomy without adenoidectomy, and male sex in patients aged ≤ 15 years.
Conclusion
Bipolar diathermy increased the risk for secondary bleedings compared to both monopolar diathermy and the cold steel with hot hemostasis technique in tonsillectomy patients. Monopolar diathermy did not significantly differ from the cold steel with hot hemostasis group regarding the bleeding rates.